OP0246 ATTAINMENT OF THE LUPUS LOW DISEASE ACTIVITY STATE IS ASSOCIATED WITH PROTECTION FROM DAMAGE ACCRUAL IN PATIENTS WITH ACTIVE DISEASE AT BASELINE. (June 2019) - Golder, Vera; Morand, Eric F.; Kandane-Rathnayake, Rangi; Huq, Molla; Nim, Hieu; Louthrenoo, Worawit; Luo, Shue Fen; Wu, Yeong-Jian; Lateef, Aisha; Sockalingam, Sargunan; Navarra, Sandra; Zamora, Leonid; et al.
Abstract : Background: The recently validated Lupus Low Disease Activity State (LLDAS) definition has been shown to have utility as a treat to target endpoint in SLE, whereby LLDAS attainment is associated with reduction in permanent damage accrual. Robust evaluation is required to ensure this protective association is not simply reflective of milder disease phenotypes being over-represented among LLDAS attainers. Objectives: To assess the effect of attainment of LLDAS on damage accrual in patients with active disease at baseline. SLEDAI-2K≥6 was chosen as this reflects clinical trial entry criteria. Methods: A prospective multinational cohort study was undertaken in 13 centres between 2013-2017. Patients with SLE were recruited, SLEDAI-2k, SELENA flare index, PGA, and medication data collected at every visit, and damage score (SLICC-ACR damage index (SDI)) collected annually. Subgroup analyses were performed to assess the effect of LLDAS on damage accrual in patients who had active disease at baseline (SLEDAI-2K≥6). Time-dependent hazards regression models were used to assess the association of attainment of LLDAS at any time point, and proportion of time in LLDAS at the 50% observed time cut-off, with accrual of irreversible end-organ damage. Results: 1, 735 patients were followed for (mean ± SD) 2.2 ± 0.9 years, totalling 12, 717 visits. LLDAS attainment was less frequent in patients with active disease at baseline (901 of 3835 visits in LLDAS, 23.5%), compared to patients with SLEDAI2-K<6 at baseline (5190 of 8845 visits in LLDAS, 58.7%), p<0.001. In contrast, compared to those with baseline SLEDAI-2K<6, patients with active disease at baseline demonstrated a stronger association of LLDAS attainment with reduction in risk of damage accrual, in visit by visit analysis (HR 0.49, 95% CI 0.28-0.86, p 0.01 vs HR 0.72, 95% CI 0.52-0.99, p 0.05), and in analysis of cumulative time spent in LLDAS (HR 0.52, 95% CI 0.33-0.83, p 0.01 vs HR 0.65, 95% CI 0.47-0.91, p 0.01). Conclusion: Despite lower attainment of LLDAS in patients with higher disease activity at baseline, the magnitude of association of LLDAS attainment with lower damage accrual was greater in this subgroup of patients compared to those less active baseline disease. This supports the validity of LLDAS as an outcome measure, in a population similar to that typically selected into clinical trials, and further highlights the potential impact of achieving a target outcome in SLE patients with active disease. Disclosure of Interests: Vera Golder: None declared, Eric F. Morand Grant/research support from: AstraZeneca, Bristol Myers Squibb, Janssen, Merck Serono, and UCB, Consultant for: AstraZeneca, Eli Lilly, Janssen, and Merck Serono, Speakers bureau: AstraZeneca, Rangi Kandane-Rathnayake: None declared, Molla Huq: None declared, Hieu Nim: None declared, Worawit Louthrenoo: None declared, Shue Fen Luo: None declared, Yeong-Jian Wu: None declared, Aisha Lateef : None declared, Sargunan Sockalingam: None declared, Sandra Navarra: None declared, Leonid Zamora: None declared, Laniyati Hamijoyo: None declared, Yasuhiro Katsumata: None declared, masayoshi harigai Grant/research support from: Tokyo Women's Medical University (TWMU) has received unrestricted research grants for Division of Epidemiology and Pharmacoepidemiology of Rheumatic Diseases from Ayumi Pharmaceutical Co. Ltd., Bristol Meyers Squib, Chugai Pharmaceutical Co. Ltd., Nippon Kayaku Co. Ltd., Taisho Toyama Pharmaceutical Co. Ltd., Mitsubishi Tanabe Pharma Corp., and with which TWMU paid the salary of MH. MH has also received research grants from AbbVie Japan GK, Eisai Co. Ltd., Takeda Pharmaceutical Co., Ltd., and Teijin Pharma Ltd., Madelynn Chan: None declared, Sean O'Neill: None declared, Fiona Goldblatt: None declared, Chak Sing Lau: None declared, Zhanguo Li: None declared, Alberta Hoi Grant/research support from: GSK, AstraZeneca, UCB and Merck Serono, Consultant for: Janssen Steering Committee, Speakers bureau: Novartis, Mandana Nikpour: None declared